2017
DOI: 10.1002/anie.201704758
|View full text |Cite
|
Sign up to set email alerts
|

Integrated In Situ Characterization of a Molten Salt Catalyst Surface: Evidence of Sodium Peroxide and Hydroxyl Radical Formation

Abstract: Sodium‐based catalysts (such as Na2WO4) were proposed to selectively catalyze OH radical formation from H2O and O2 at high temperatures. This reaction may proceed on molten salt state surfaces owing to the lower melting point of the used Na salts compared to the reaction temperature. This study provides direct evidence of the molten salt state of Na2WO4, which can form OH radicals, using in situ techniques including X‐ray diffraction (XRD), scanning transmission electron microscopy (STEM), laser induced fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 35 publications
3
57
0
Order By: Relevance
“…We emphasize that radical-mediated selective oxidation mechanisms have been previously proposed in the literature. The group of Marin extensively studied the reaction kinetics of oxidative methane coupling (OCM) in empty reactors and using Li/MgO catalysts, and they proposed an overall mechanism coupling surface and gas-phase reactions. , Takanabe and co-workers proposed that hydroxyl radicals play an important role during OCM using Mn/Na 2 WO 4 /SiO 2 catalysts as well as during ODH of ethane. Leveles et al developed a reaction kinetics study of Li/Dy/MgO catalysts for ODH of propane and identified reaction regimes where homogeneous reactions play a comparable role to surface-catalyzed propane conversion. Furthermore, their observed partial pressure dependencies show trends similar to those observed on hBN catalysts, ,, albeit with a significantly higher selectivity toward CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…We emphasize that radical-mediated selective oxidation mechanisms have been previously proposed in the literature. The group of Marin extensively studied the reaction kinetics of oxidative methane coupling (OCM) in empty reactors and using Li/MgO catalysts, and they proposed an overall mechanism coupling surface and gas-phase reactions. , Takanabe and co-workers proposed that hydroxyl radicals play an important role during OCM using Mn/Na 2 WO 4 /SiO 2 catalysts as well as during ODH of ethane. Leveles et al developed a reaction kinetics study of Li/Dy/MgO catalysts for ODH of propane and identified reaction regimes where homogeneous reactions play a comparable role to surface-catalyzed propane conversion. Furthermore, their observed partial pressure dependencies show trends similar to those observed on hBN catalysts, ,, albeit with a significantly higher selectivity toward CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to this, a significant broadening of the ν sym (W−O) stretching mode of Na 2 WO 4 at 923 cm −1 was observed in the Raman spectrum of the catalyst above the melting point of Na 2 WO 4 (Figure A, top). Both, Takanabe et al., and Yu. et al., reported similar observations, describing a reversible disappearance and intensity loss of the characteristic Raman bands for Na 2 WO 4 supported on TiO 2 and CeO 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The source of oxygen has been attributed to manganese oxide, or any unspecified lattice oxygen . Potentially more decisive is the release of an active form of sodium oxide species that has been proposed to catalyse the oxidative coupling of methane by generation of OH radicals at high temperatures, presumably under involvement of homogeneous gas‐phase reactions due to the high volatility of sodium compounds under operation conditions …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations